Achieving Alignment between Institutions and Technology, the Case of Radio Spectrum. Issue 2 (June 2013) - Anker, Peter; Lemstra, Wolter
This paper deals with the alignment between institutions and technology in the case of the radio spectrum. The current theories on co-evolution and coherence address the need for alignment, but they don't resolve how this alignment could be achieved. This paper emphasizes the role of the actors to achieve alignment. This perspective is illustrated through a review of historical cases of changes in radio spectrum management and the introduction of new (radio) technology. It is followed by a proposal how to deal with alignment in the case of the introduction of cognitive radio, a promising new radio technology that could be used to improve spectrum utilization.